Влияние параметров анизотропии упругой линзы на ее фокусирующие свойства - Иванченко, Г. М. (НТУ "ХПИ", 2006)
The cases of focusing of a plane unstationary discontinuous wave by the surfaces of a plane-convex transversally isotropic elastic lens in a transversally isotropic medium are examined. Dependence of position of focusing zones of the wave on the values of parameters of anisotropy of the lens medium is exlored
Keywords: оптические приборы; световые лучи; вектор поляризации; квазипродольная волна